2020
DOI: 10.21203/rs.3.rs-18001/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with the burden of family caregivers  of elderly patients with femoral neck fracture: a cross-sectional study

Abstract: Background: This study aimed to study the factors associated with caregiver burden among caregivers of elderly patients with femoral neck fracture. Methods: This cross-sectional study was based on a non-probabilistic sampling of 183 elderly postoperative patients (aged 65 years or older) with femoral neck fracture who were hospitalized in the orthopaedic centre in our hospital and their family caregivers. Data were collected from January 2016 to June 2019. Patients and family caregivers completed the sociodemo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Most of the caregivers, in both groups, were adults, urban, elderly, majority being females and were either spouse/parents/children of the patients contrary in a study by Xiao et al had observed that majority were elderly (69.28±7.19 years), males and 84% were spouses of the patients. 12 However, these demographic characteristics did not aggravate the burden of the caregivers in another study by Li et al 13 A variety of physical symptoms were reported by the caregivers which was almost similar in both ICU and non-ICU patients. Identically, studies on caregivers of hospitalized persons had reported that long-term caregiving can adversely affect caregivers' physical health.…”
Section: Discussionmentioning
confidence: 83%
“…Most of the caregivers, in both groups, were adults, urban, elderly, majority being females and were either spouse/parents/children of the patients contrary in a study by Xiao et al had observed that majority were elderly (69.28±7.19 years), males and 84% were spouses of the patients. 12 However, these demographic characteristics did not aggravate the burden of the caregivers in another study by Li et al 13 A variety of physical symptoms were reported by the caregivers which was almost similar in both ICU and non-ICU patients. Identically, studies on caregivers of hospitalized persons had reported that long-term caregiving can adversely affect caregivers' physical health.…”
Section: Discussionmentioning
confidence: 83%